Energy and protein requirements of commercial broilers in winter - NAGRA, S S; CHAWLA, J S (The Indian Journal of Animal Sciences, 2013)
Energy and protein requirements of commercial (IBL-80) broilers were determined under the cold climatic conditions In a 3 x 3 factorial design using 20, 22 and 24% protein levels, each with 2 500, 2 700 and 2900 Kcal metabolizable energy (ME) per kg diet, A single diet feeding programme was followed from day-old to 56 days of age. Protein content of the diet had significant (P